229k views
9 votes
Factor and simplify
sec⁴x-tan⁴x÷sec²x + tan²
X
Verify the identity​

User VinoPravin
by
6.1k points

1 Answer

8 votes

Answer:

1

Explanation:

sec⁴x-tan⁴x÷sec²x + tan²X

= sec⁴x-tan⁴x/sec²x + tan²X

= (sec²x)²-(tan²x)²/sec²x + tan²X

Using the difference of two square

a² - b² = (a+b)(a-b)

(sec²x)²-(tan²x)² = (sec²x + tan²X)(sec²x - tan²X)

= (sec²x)²-(tan²x)²/sec²x + tan²X

= (sec²x + tan²X)(sec²x - tan²X)/sec²x + tan²X

= sec²x - tan²X

Also sec²X = 1 + tan²X

Substitute

= 1 + tan²X- tan²X

= 1

Hence the value of the expression is 1

User Naveen Chauhan
by
4.8k points